2008
DOI: 10.1074/jbc.m708697200
|View full text |Cite
|
Sign up to set email alerts
|

An NADPH Sensor Protein (HSCARG) Down-regulates Nitric Oxide Synthesis by Association with Argininosuccinate Synthetase and Is Essential for Epithelial Cell Viability

Abstract: NADPH is an important cofactor in many biosynthesis pathways that control fundamental cellular processes. We recently determined the crystal structure of HSCARG, with functions previously unknown, and demonstrated it is an NADPH sensor, which undergoes restructuring and redistribution in response to changes of intracellular NADPH/NADP levels. In this study, we identified argininosuccinate synthetase (AS), a rate-limiting enzyme in nitric oxide synthesis, as capable of associating with HSCARG and demonstrated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 50 publications
1
60
0
Order By: Relevance
“…Proteomic analysis of RAW 264.7 macrophages suggests that TNFR1-enriched fractions are also enriched in proteins mediating the antioxidant, inflammatory, cytoskeletal, and metabolic functions of macrophages. Of particular relevance, antioxidants are likely to be protective and included NmrA-like family domain containing 1, a NADPH oxidase sensor that can decrease NO synthesis by association with argininosuccinate synthetase and, thereby, increase cell survival (40). In addition, annexin A1 can inhibit inducible NO synthase expression in macrophages and can limit phospholipase A2 activity (41).…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic analysis of RAW 264.7 macrophages suggests that TNFR1-enriched fractions are also enriched in proteins mediating the antioxidant, inflammatory, cytoskeletal, and metabolic functions of macrophages. Of particular relevance, antioxidants are likely to be protective and included NmrA-like family domain containing 1, a NADPH oxidase sensor that can decrease NO synthesis by association with argininosuccinate synthetase and, thereby, increase cell survival (40). In addition, annexin A1 can inhibit inducible NO synthase expression in macrophages and can limit phospholipase A2 activity (41).…”
Section: Discussionmentioning
confidence: 99%
“…13 HSCARG is essential for epithelial cell viability, binds NADPH much more strongly than NADP þ and may link changes in the NADP þ : NADPH ratio to modulation of the production of the important cell signaling molecule nitric oxide. [14][15][16] Microcalorimetry experiments showed that NmrA binds NAD þ and NADP þ with similar affinity but has a greatly reduced affinity for NADH and NADPH. The structure of NmrA in a complex with NADP þ has shown how repositioning a His 37 sidechain allows the different conformations of NAD þ and NADP þ to be accommodated.…”
Section: Introductionmentioning
confidence: 99%
“…The negative effect of HSCARG on NO production is enhanced when the intracellular NADPH/NADP ϩ ratio decreases. In response to DHEA or SNAP treatment, HSCARG translocates from the cytoplasm to the nucleus (28,29), suggesting that HSCARG may exert regulatory functions in the nucleus as well.…”
mentioning
confidence: 99%
“…In our previous work, we have solved the crystal structure (29) and found that it is involved in regulation of NO production (28). HSCARG interacts with argininosuccinate synthetase, a rate-limiting enzyme in NO synthesis, and down-regulates NO synthesis through repression of argininosuccinate synthetase activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation